Walk the blue line [compact disc, unabridged] - Patterson, James, 1947-; Eversmann, Matt; Mooney, Chris (Chris C.) (Hachette Audio, 2023)
The men and women who serve and protect our homes, families, and communities reveal what it's like to wear the uniform in their most dramatic true stories, told in their own unforgettable words.